Prevalence of Metabolic Syndrome in Patients With Type 2 Diabetes Mellitus in a Tertiary Care Hospital - Shakya, Dipesh; KC, Vijay (Medical Journal of Shree Birendra Hospital, 2019)
Introduction: Diabetes mellitus is associated with various metabolic disorders, which leads to the progression of the disease and its complications. The aim of the study is to find out prevalence of metabolic syndrome and its association with the components and demographic variables.Methods: This cross-sectional study was conducted among diabetes mellitus patients at a Tertiary level teaching hospital over a period of one year (April 2015 to March 2016). The study involved the use of a questionnaire to obtain information on diabetes by performing anthropometric measurements and corroborating it with respective blood samples collected for the measurement of biochemical parameters, fasting blood glucose and lipid profile. Metabolic syndrome was defined according to the current guidelines, revised in 2005 by the National Heart, Lung and Blood Institute and the American Heart Association. Statistical Package for the Social Sciences Version 20 was used as a tool for statistical analysis.Results: This cross-sectional study involved 200 type 2 diabetes mellitus patients. The prevalence of metabolic syndrome was 71% in the studied Nepalese population. Central obesity (77.5%) and hypertension (76.8%) were the commonest risk factors. It was followed by dyslipidemia among which 65.5% had high triglyceride level and 50.7% had low level of high density lipoprotein cholesterol. Higher prevalence of metabolic syndrome was seen in male patients with type 2 diabetes which accounted for 84 (73.3%). Three components of metabolic syndrome were seen among 70 (35%) and five components among 29 (14.5%) patients. Among the patients who were studied, the age group 45 to 54, 55 to 64 and 65 to 74 years had 14 (20%), 20 (28.6%) and 19 (27.1%) of more than three components of metabolic syndrome respectively.Conclusions: The prevalence of metabolic syndrome was 71% among the patients with type 2 diabetes, where high prevalence was seen among males. In our study central obesity and hypertension along with increasing age were the most common component causing metabolic syndrome.